Lessons learned: Coaches` perceptions of a pilot e-mentoring programme - Grant, M. A.; Bloom, G. A.; Lefebvre, J. S. (International Sport Coaching Journal, 2020)
The purpose of this study was to examine mentor and mentee perceptions of the viability of a pilot e-mentoring programme for U.S. lacrosse (USL) coaches. Twelve mentees and 12 mentors were paired into dyads, met at a national coaching convention, and were directed to continue their mentoring relationship for up to 6 months via an online platform. Semistructured postprogramme interviews were conducted with four mentors and six mentees at the conclusion of the mentoring relationships. Interviews were transcribed verbatim and analysed via thematic analysis. Results showed that mentors and mentees experienced many of the benefits, barriers, and advantages found in traditional mentoring and e-mentoring relationships. Of interest were three key findings in which trust and respect was quickly experienced by participants, equity within the relationship created collegiality, and technology barriers limited effective teaching methods. Based on the results, practical implications for e-mentoring programmes are presented.